3 - Women and Liberal Peacebuilding in Post- Conflict Northern Uganda: community social work agenda revisited? - Eric Awich Ochen, (African Sociological Review, 2017)
This paper examines women’s participation in post-conflict peacebuilding activities within the neo-liberal peace theory and framework. Using qualitative approach, the study gathered information from 40 women and several key informants working and living in post-conflict northern Uganda. The paper utilizes this information in reflecting on how women live in and engage with their communities in post-conflict settings, and also assess the actual actions and initiatives that women develop in post-conflict situation, the space available to them and the emergent context. The paper also analyses the extent to which these factors shape community post-conflict adjustments. Key challenges affecting women’s participation in the peacebuilding processes, mainly at grassroots and community levels are examined. The major conclusion of the paper is that liberal peacebuilding approach does not fully espouse, embrace or explain issues of critical consciousness, social and strategic agency nor does it prepare the women to effectively engage their society. I argue that this limitation and omission do not adequately prepare women to confront social issues and oppressive practices as well as challenge certain traditions and power structures, issues that are hall marks of community based social work.